Chaya (native plant known as tree spinach) introduced in school feeding programme in Chiquimula, Guatemala - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
In 2019, chaya was approved as an ingredient in 2 of the 20 planned menus and was suggested as a potential substitute for other vegetables that were already part of the school meal, including spinach, chipilín, and black nightshade. We waited to update this innovation until new reports were published.